2018
DOI: 10.1177/1833358318777713
|View full text |Cite
|
Sign up to set email alerts
|

The District Health Information System (DHIS2): A literature review and meta-synthesis of its strengths and operational challenges based on the experiences of 11 countries

Abstract: This study highlighted specific strengths in the technical and functional aspects of DHIS2 and also drew attention to particular challenges and concerns. These results provide a sound evidence base for decision makers and policymakers to enable them to make more accurate decisions about whether or not to use the DHIS2 in the health system of their country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
205
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(227 citation statements)
references
References 11 publications
2
205
0
4
Order By: Relevance
“…DHIS2 allows facilities and administrative areas to report health indicators allowing for collection and aggregation of health data, including cases of PE/E. Although there are certain valid concerns regarding the quality of DHIS2 data, overall, it presents an opportunity for analysis of routinely collected health surveillance data (Dehnavieh et al 2019). Routinely collected data from health facilities is relatively inexpensive but relies on people and institutions to enter data and ensure its completeness, consistency, and timeliness.…”
Section: Opportunities For Surveillance Datamentioning
confidence: 99%
See 1 more Smart Citation
“…DHIS2 allows facilities and administrative areas to report health indicators allowing for collection and aggregation of health data, including cases of PE/E. Although there are certain valid concerns regarding the quality of DHIS2 data, overall, it presents an opportunity for analysis of routinely collected health surveillance data (Dehnavieh et al 2019). Routinely collected data from health facilities is relatively inexpensive but relies on people and institutions to enter data and ensure its completeness, consistency, and timeliness.…”
Section: Opportunities For Surveillance Datamentioning
confidence: 99%
“…Health surveillance data can be utilized in many ways, including to document or track progress towards public health goals, monitor the epidemiology and magnitude of a certain disease, serve as an early warning system to detect impending public health emergencies, and potentially to inform the targeting of interventions (Dehnavieh et al 2019). Health surveillance data and remotely sensed data could be effective tools to explore health and environment associations, such as between salinity and PE/E, especially if they can be routinely linked to allow for real-time detection of hotspots to inform program targeting.…”
Section: Opportunities For Surveillance Datamentioning
confidence: 99%
“…Hence, it cannot handle the challenges of a Department like Surgery The rationale for DHMIS has been that the availability of operational, effective and efficient health management information systems is an essential component of the required district management capacity. The logic is that effective and efficient HMIS will provide district health managers with the information required to make effective strategic decisions that support district performance and sustainability in these decentralized health systems [23]. This system is mainly focused on the management information part.…”
Section: ) Implementation Of Records Systems In Hospitalsmentioning
confidence: 99%
“…While early RHISs were established using paper-based health facility reports, newer web-based systems have been adopted in many LMICs over the last decade 13,14 . The most common of these is the District Health Information System 2 (DHIS 2) platform, which is used as the foundation for the national health management information systems (HMIS) in 46 countries and piloted in another 21 countries 15 . Studies have shown that the implementation of newer information and communication technology systems, along with supportive feedback mechanisms to encourage their use in routine practice, can lead to substantial improvements in RHIS reporting and data quality 5,13,16,17 .…”
Section: Introductionmentioning
confidence: 99%